PREVENTION OF COVID-19 INFECTION DURING DENTUREREPAIR FOR DENTAL ARTISAN IN LAMONGAN CITY: PENCEGAHAN INFEKSI COVID-19 SAAT REPARASI GIGITIRUAN PADA PARA TUKANG GIGI DI KABUPATEN LAMONGAN - Endang Kusdarjanti; Okti Setyowati; anisa nurhalimah; Sujati; Eny Inayati (Darmabakti Cendekia: Journal of Community Service and Engagements, 2023)
Background: The lack of dentists in rural and remote areas has resulted in the dental profession being still in demand and in great demand in these areas. They do not have basic knowledge of dentistry and get that knowledge self-taught. The low knowledge of dental artisans on health sciences can cause the actions they take to endanger themselves and the health of consumers. Objective: To provide counseling and workshops on preventing Covid-19 infection during denture repair and manufacture of UV Sterilizers for dental artisans who are members of the Forum Komunitas Bikin Gigi (FOKABIG) in Kabupaten Lamongan in order to know the dangers of Covid-19 infection when performing dental repairs and other efforts. what to do to prevent it. Methods: Counseling and workshop on prevention of Covid-19 infection during denture repair and manufacture of UV sterilizer box. Results: This community service program was held in desa Candisari Kecamatan Sambeng Kabupaten Lamongan y by conducting counseling when performing denture repairs to avoid transmission of Covid-19 infection and workshops on making UV sterilization boxes for dental artisans who are members of the Forum Komunitas Bikin Gigi (FOKABIG). Conclusion: After attending counseling and workshops to prevent Covid-19 infection during denture repair and manufacture of UV box sterilizers, it is hoped that dental technicians will be able to carry out and run this program and run it regularly in doing so so as to prevent infections that can occur. Keywords: disinfection, denture, resin above, dental artisan